The effect of prenatal yoga on pubic bone pain in pregnant women in the third trimester - Rosidah, Idah; Triana Indrayani; Risza Choirunissa (KHD-Production, 2025)
Pubic bone pain is one of the discomforts that occurs in pregnant women in the third trimester. This problem often occurs in pregnant women, especially in the third trimester. Pharmacological and non-pharmacological methods can be used to manage pubic bone pain. Non-pharmacological pain management can be done in several ways, including relaxation, acupressure, and prenatal yoga. Prenatal yoga is one of the modifications of hatha yoga adapted to pregnant women's conditions. This study aims to determine the effect of prenatal yoga on pregnant women in the third trimester in overcoming pubic bone pain in the control and intervention groups. The method for this study uses quasi-experimental research, which uses a pre- and post-test design with a control group design. The sample in this study amounted to 50 pregnant women in the third trimester, consisting of 25 pregnant women in the intervention group and 25 pregnant women in the control group. The sampling technique used was purposive sampling. This research instrument used pain measurement with the NRS. Due to abnormal distribution, the data were analyzed using descriptive statistics and non-parametric tests, namely the Wilcoxon test. The results of the study showed that prenatal yoga affected pubic bone pain in third-trimester pregnant women, with a value of P = 0.000. Prenatal yoga was able to reduce pubic bone pain in pregnant women in the third trimester. The researcher was then able to provide both pharmacological and non-pharmacological treatment to pregnant women in the third trimester who experienced pubic bone pain.